Floating obsidian and its implications for the interpretation of Pacific prehistory - Spennemann, Dirk H. R.
A piece of pumice among drift material on Nadikdik Atoll, Marshall Islands, in far Micronesia had a large chunk of flakeable obsidian attached. As the atoll had been devastated by a typhoon and associated storm surge in 1905, the piece must have arrived by sea within the last 90 years. This and similar incidences of raw materials distributed by ocean drift show how sea-borne dispersal cannot be excluded offhand in the occurrence of obsidian in far-flung places, commonly attributed to human transport.